Understanding the relationship between AI and gender on social TV content selection - Habes, Mohammed; Alhazmi, Amal Hassan; Elareshi, Mokhtar; Attar, Razaz Waheeb (Frontiers in Communication, 2024)
As technological advancements continue to shape our daily lives, and social TV has emerged as an interactive platform that fosters connections between families and friends. This study investigates the selection of social TV content by examining the influence of AI and other contributing factors, with gender proposed as a mediating factor. Involving 300 students from two randomly selected public universities in Irbid, Jordan, data were collected through an online survey with self-reported responses. The study revealed that AI enhances characteristics such as information gathering, social awareness, and knowledge sharing, subsequently affecting user attitudes and content selection on social TV platforms. Both AI and user attitudes significantly contribute to content selection, while gender acts as a mediator, influencing AI integration and attitudinal shifts. Ultimately, AI provides seamless access to preferred content and improves ease of use, enriching content recommendation systems and fostering increased user interest and satisfaction. This positive experience with AI services shapes user attitudes towards technology. This study offers a comprehensive examination of the intersection between AI, gender, attitudes, and social TV content selection within the context of Jordanian young users, marking a pioneering contribution to the field of media studies in the MENA region.